PENGARUH KOMPETENSI DAN KARAKTERISTIK PEKERJAAN TERHADAP KEPUASAN KERJA DENGAN MOTIVASI SEBAGAI MEDIASI ( Studi Pada Pegawai Dinas Pendidikan Kabupaten Pati ) - Ahmadi, Ahmadi; Rijanti, Tristiana (Jurnal Ilmiah Telaah Manajemen, 2015)
The purpose of this study to determine the effect of competencyand job characteristic on job satisfaction mediated by the work motivationat Dinas Pendidikan Kabupaten Pati. This research was conducted with a sensus method and implemented in Dinas Pendidikan Kabupaten Pati. Technical test data used in this study include validitas test, reliability test, multiple regression analysis, t test, and mediation test to verify and prove the hypothesis of the research. From the analysis and discussion show that competency does not influence on work motivation,job characteristic positively significanly influence on work motivation, competency does not influence on job satisfaction, job characteristicpositively significantly influence on job satisfaction and work motivationpositively significantly influence on job satisfaction. Motivation is not proven as a mediation variable of competence influence on job satisfaction while the influence of characteristic to job satisfaction motivation proved as mediation variableKeywords: Competency, Job characteritics, Motivation and Job Satisfaction.